High-frequency transformer-link inverter with regenerative snubber - Toh, LS; Salam, Zainal; Ramli, Mohd zulkifli (2006)
This work proposes a bidirectional high-frequency link inverter using center-tapped high-frequency transformer. The topology also incorporates a regenerative snubber to clamp the high voltage spikes due to the leakage inductance of the transformer. The closed-loop control method used is deadbeat control, which provides fast response and low harmonic distortion, even under nonlinear loads. A 1 kVA prototype inverter is built and the workability of the system is experimentally verified